2012
DOI: 10.1155/2012/287608
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Microwave Radiation on Prickly Paddy Melon (Cucumis myriocarpus)

Abstract: The growing list of herbicide-resistant biotypes and environmental concerns about chemical use has prompted interest in alternative methods of managing weeds. This study explored the effect of microwave energy on paddy melon (Cucumis myriocarpus) plants, fruits, and seeds. Microwave treatment killed paddy melon plants and seeds. Stem rupture due to internal steam explosions often occurred after the first few seconds of microwave treatment when a small aperture antenna was used to apply the microwave energy. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…Microwaves. Focusing microwaves onto weeds using a small horn antenna has been suggested as a novel weed management tool (Brodie et al 2012a). The difficulty associated with this method is how to precisely direct the microwaves within a narrow spatial band suitable for targeting individual weeds.…”
Section: Laser Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwaves. Focusing microwaves onto weeds using a small horn antenna has been suggested as a novel weed management tool (Brodie et al 2012a). The difficulty associated with this method is how to precisely direct the microwaves within a narrow spatial band suitable for targeting individual weeds.…”
Section: Laser Bmentioning
confidence: 99%
“…The energy requirement would be 67 J per weed, including an efficiency factor of 75% for the microwave-producing magnetron. This is based on a test conducted on the five stems of a paddymelon (Cucumis myriocarpus Naudin) (Brodie et al 2012a). Each stem was treated with 200 J cm −2 using an aperture size of 86 mm by 20 mm, resulting in a total energy consumption of 18 MJ ha −1 .…”
Section: Laser Bmentioning
confidence: 99%
“…In the case of a cylindrical object, such as a plant stem, the microwave's electric field distribution created by a horn antenna [21] can be described by: The resulting temperature distribution can be described by [75] : [59,73,76,77]. Aperture size of the horn applicator profoundly affects the treatment time needed to kill plants, with the smaller aperture needing much less time to provide a lethal dose; however the total energy density needed to kill the plants (microwave output power density multiplied by treatment time) was the same irrespective of the horn aperture size.…”
Section: Effect Of Microwave Heating On Seeds and Plantsmentioning
confidence: 99%
“…The authors concluded that the long exposure to microwave radiation, even at very low power densities, was sufficient to dehydrate the seedlings and inhibit their development. On the other hand, recent studies on fleabane (Conyza bonariensis) and paddy melon (Cucumis myriocarpus) [75,77] have revealed that a very short (less than 5 second) pulse of microwave energy, focused onto the plant stem, was sufficient to kill these plants. In both cases, rapid dehydration of the plant tissue appears to be the cause of death.…”
Section: Effect Of Microwave Heating On Seeds and Plantsmentioning
confidence: 99%
See 1 more Smart Citation